Dissemination of a simulation-based mastery learning intervention reduces central line-associated bloodstream infections. Issue 9 (14th March 2014) - Barsuk, Jeffrey H; Cohen, Elaine R; Potts, Steven; Demo, Hany; Gupta, Shanu; Feinglass, Joe; McGaghie, William C; Wayne, Diane B
Abstract : Background: Approximately 41 000 central line-associated bloodstream infections (CLABSI) occur annually in US hospitals. We previously developed a simulation-based mastery learning (SBML) curriculum in central venous catheter (CVC) insertion that significantly reduced CLABSI rates. In this study, we evaluated the effect of dissemination of the SBML curriculum on trainee skills and CLABSI rates at a community hospital. Methods: The authors performed a cohort study of residents who rotated in the intensive care unit (ICU) at Mercy Hospital and Medical Center from September 2010 to May 2012. Residents underwent an SBML CVC insertion curriculum and were required to meet or exceed a minimum passing score on a simulated internal jugular (IJ) and subclavian (SC) CVC insertion before ICU patient care. Infection control personnel measured CLABSI rates in the ICU before and after the educational intervention. Results: Residents scored a mean IJ pretest of 35.5% (10.29/29, SD=8.30) compared with a post-test mean of 93.0% (26.96/29, SD=1.50; p<0.001). Their mean SC pretest score was 23.0% (6.68/29; SD=9.58) and increased to 96.1% (27.88/29, SD=1.41) at post-test (p<0.001). Patients experienced 3.82 infections per 1000 catheter-days (20 infections in 5235 catheter-days) in the ICU in the 23 months before the educational intervention. During the 21 months after the intervention, there were 1.29 infections per 1000 catheter-days (six infections in 4670 catheter-days (p=0.019)). The incidence rate ratio derived from the Poisson regression was 0.26 (95% CI 0.09 to 0.74) after controlling for Acute Physiology and Chronic Health Evaluation III score indicating that there was a 74% reduction in the incidence of CLABSI in the medical ICU after the intervention. Conclusions: This study demonstrates successful dissemination and implementation of a CVC SBML curriculum and shows that rigorous medical education is a powerful quality improvement tool.